Assessing species and stage specific effects of preservation on fish oocytes over different temporal scales - RAKKA, M.; GANIAS, K. (Mediterranean Marine Science, 2015)
This study assessed the effect of 10% neutral buffered formalin and of three ethanol solutions of different concentration on Mediterranean sardine and European anchovy oocytes over several temporal scales (days, weeks, months). The two species exhibit differences both in the elemental composition and the shape of their oocytes which further allowed an appraisal of oocyte shrinkage dynamics in relation to oocyte shape, developmental stage and composition. We showed that the effect of the preservative on oocyte size is stage specific while different preservation periods of ovarian material might lead to discrepancies among studies.